Testing for Minimal Consciousness in Complex Partial and Generalized Tonic-Clonic Seizures - McPherson, Alison (2012)
Impaired consciousness in epilepsy has a major negative impact on quality of life. Prior work suggests that complex partial seizures (CPS) and generalized tonic-clonic seizures (GTCS), which both cause loss of consciousness, affect similar fronto-parietal networks. Milder involvement in CPS than in GTCS may spare some simple behavioral responses, resembling the minimally conscious state. However, this difference in responses has not been rigorously tested previously. During video/EEG monitoring, we administered a standardized prospective testing battery including responses to questions and commands, as well as tests for reaching/grasping a ball and visual tracking in 27 CPS (14 patients) and 7 GTCS (6 patients). Behavioral results were analyzed in the ictal and post-ictal periods based on video review. During both CPS and GTCS, patients were unable to respond to questions or commands. However, during CPS patients often retain minimally conscious ball grasping and visual tracking responses. Patients were able to successfully grasp a ball in 60% or to visually track in 58% of CPS, and could carry out both activities in 52% of CPS. In contrast, during GTCS preserved ball grasp (10%), visual tracking (11%) or both (7%) were all significantly less than in CPS. Post-ictal ball grasping and visual tracking were also somewhat better following CPS than GTCS. These findings suggest that impaired consciousness in CPS is more similar to minimally conscious state than to coma. Further work may elucidate the specific brain networks underlying relatively spared functions in CPS, ultimately leading to improved treatments aimed at preventing impaired consciousness.